Long-term inactive data retention through tape storage technology - Vican, Ivan (Array, 2009)
Increasingly the need to retain digital documents indefinitely for legal, administrative or historical purposes is simply leading to a “save everything forever” approach. The authors argue that due to the technological reasons it is much easier to preserve large amount of documents in the electronic than in the paper form. Thus the selection procedures tend to be less restrictive than they used to be. Nevertheless, for most organizations it would be impossible to sustain this data growth forever. Archives, libraries, museums, institutions holding cultural heritage, as well as other companies and firms, are implementing solutions for creating digital archives, digital libraries, digital repositories and other types of storage systems aiming at long-term preservation of digital materials. Most of the data held in such systems are inactive for a long time, i.e. only a small set of data is frequently retrieved. Therefore, due to the specific needs of every organization, the storage planning process and the technology that is going to be used for storage and long-term preservation requires individual approach. The focus of this paper is on the retention of the long-term inactive data through tape storage technology. The authors will discuss current state of the art tape storage capabilities, and their advantages and disadvantages as a long-term storage and preservation solution.